2023
DOI: 10.1002/jsp2.1282
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 differentially controls inflammatory cytokine networks during static and dynamic compression of the intervertebral disc

Garrett W. D. Easson,
Alireza Savadipour,
Christian Gonzalez
et al.

Abstract: BackgroundThe ion channel transient receptor potential vanilloid 4 (TRPV4) critically transduces mechanical forces in the IVD, and its inhibition can prevent IVD degeneration due to static overloading. However, it remains unknown whether different modes of loading signals through TRPV4 to regulate the expression of inflammatory cytokines. We hypothesized that TRPV4 signaling is essential during static and dynamic loading to mediate homeostasis and mechanotransduction.MethodsMouse functional spine units were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(142 reference statements)
0
2
0
Order By: Relevance
“… 163 Sustained compressive loading of the IVD resulted in elevated NF‐κB activity, IL‐6 and vascular endothelial growth factor A (VEGFA) production, and degenerative changes to the ECM, whereas TRPV4 inhibition during loading mitigated the changes in inflammatory cytokines and protected against IVD degeneration. 166 These results indicate that mechano‐osmotic signaling via TRPV4 plays an important role in both short‐ and long‐term adaptations of the IVD and could be targeted to prevent load‐induced IVD degeneration. A number of studies have demonstrated the responsiveness of AF and NP cells to short duration or long term dynamic compression which can result in a combination of anabolic and catabolic responses that may result in ECM remodeling or enhanced matrix synthesis.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“… 163 Sustained compressive loading of the IVD resulted in elevated NF‐κB activity, IL‐6 and vascular endothelial growth factor A (VEGFA) production, and degenerative changes to the ECM, whereas TRPV4 inhibition during loading mitigated the changes in inflammatory cytokines and protected against IVD degeneration. 166 These results indicate that mechano‐osmotic signaling via TRPV4 plays an important role in both short‐ and long‐term adaptations of the IVD and could be targeted to prevent load‐induced IVD degeneration. A number of studies have demonstrated the responsiveness of AF and NP cells to short duration or long term dynamic compression which can result in a combination of anabolic and catabolic responses that may result in ECM remodeling or enhanced matrix synthesis.…”
Section: Introductionmentioning
confidence: 81%
“…While the TRPV4 ion channel can regulate secretion of inflammatory mediators contributing to IVD degenerative changes and pain, 166 , 173 a recent study demonstrated that activation of the innate immune response through toll‐like receptors (TLRs) can also contribute to deleterious IVD changes in IVDD. 174 Mechanically loaded rat IVDs displayed increased pro‐inflammatory mediators with static but not dynamic loading.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms that promote immune cell infiltration into the IVD due to injury were not investigated. Previous work has demonstrated that applying damaging mechanical loads promotes production of neutrophil-recruiting chemokines and mechanosensitive ion channel activation temporally regulates immune cell-recruiting chemokines 51 . Endogenous production of immune-related chemokines from IVD cells could partially explain how immune cells home to injured IVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a rabbit model, Fainor et al show that perturbations in disc biomechanics not only cause local pathological remodeling in structures such as the vertebral endplates, but also in adjacent structures such as the facet joints 2 . Easson et al identified the ion channel transient receptor potential vanilloid 4 (TRPV4) as performing a critical role in mediating the interplay between inflammation and loading in mouse intervertebral discs 3 …”
Section: Special Issue Highlightsmentioning
confidence: 99%